Enhanced antibacterial and photocatalytic degradation of reactive red 120 using lead substituted ZnO nanoparticles prepared by ultrasonic-assisted co-precipitation method. Issue 11 (1st August 2020) - Gnanamozhi, P.; Rajivgandhi, G.; Alharbi, Naiyf S.; Kadaikunnan, Shine; Khaled, Jamal M.; Almanaa, Taghreed N.; Pandiyan, V.; Li, Wen-Jun
Abstract: Lead (Pb) substituted ZnO nanoparticles were prepared using the ultrasonic-assisted co-precipitation method to enhance the degradation efficiency of reactive red 120 and zone of inhibition of pathogens. The structural, optical, and morphological properties of different concentrations of Pb substituted ZnO nanoparticles were characterized. The result confirmed the formation of Pb: ZnO from the structural, optical, and morphological characterization. The dynamic light scattering spectra show that prepared particles were in the range of 50-110 nm. Scanning electron microscopic image exhibited the formation of hexagonal and spindle-like particles with a size less than 100 nm for a 5% Pb substituted sample. The reflectance and bandgap energy of the Pb substituted ZnO nanoparticles decreased with increasing the Pb concentration. The photocatalytic dye degradation of 5% Pb substituted ZnO nanoparticles showed a higher degradation rate of reactive red 120, and it degraded within 120 min. The antibacterial activity of the 5% Pb substituted samples has higher zone of inhibition of 13 mm. The antibacterial, photocatalytic dye degradation, and antibacterial activity results confirmed that 5% Pb substituted ZnO nanoparticles will be the efficient photocatalyst for the degradation of reactive red 120 and commercial use.